Parry syllogisms - Johnson, Fred (Frederick A.), author; Duke University Press, publisher (Colorado State University. Libraries, 1999)
Parry discusses an extension of Aristotle's syllogistic that uses four nontraditional quantifiers. We show that his conjectured decision procedure for validity for the extended syllogistic is correct even if syllogisms have more than two premises. And we axiomatize this extension of the syllogistic.
Keywords: subsystem of classical logic (including intuitionistic logic); logic with extra quantifiers and operators